Pengaruh Variasi Jumlah Tumbukan Menggunakan Aspal Emulsi Tipe CRS Dan Aspal Minyak Penetrasi 60/70 Pada Campuran Aspal Concrete – Wearing Course (AC-WC) Dengan Perendaman Berulang - Herman, Herman; Mallawangeng, Tamrin; Yunianti, Nur Hadijah (Program Studi Teknik Sipil Universitas Bosowa, 2025)
The purpose of the study was to determine the nature and characteristics of the effect of variations in the number of collisions on the asphalt concrete mixture with repeated immersion and determine the amount by using emulsified asphalt of CRS type and 60/70 penetration oil asphalt. The independent variable in this study is the variation of the number of collisions in the compaction of asphalt concrete as much as 2x65, 2x75, and 2x85, with Optimum Asphalt Content of 7%. The test method refers to the General Specifications of Highways 2018.The type of mixture used is (Asphalt Concrete - Wearing Coarse). The performance was measured by testing Density, Stability, Flow, marsgall Quontient, voids in mixture (VIM), voids filled with asphalt (VFB), and voids in aggregate (VMA). The asphalt content used was 7%, then repeated immersion was carried out with variations of 3 days, 7 days, and 14 days of immersion. The results of the study show that variations in the number of collisions can affect the stability value where the higher the collision variation, the value of density, stability, marshall quotient, and the value of VFB increases with the addition of the number of collisions. While using asphalt oil and asphalt emulsion with repeated immersion variations, it can be seen that the value of density, stability, Marshall quotient, and VFB value decreased with each immersion variation. The values of flow, VIM, and VMA increased with each repeated immersion variation. this applies to any variation in the number of collisions.